POLITICAL COMPETITION IN RIAU: A REVIEW OF CRITICAL DISCOURSE ANALYSIS - Rizki Erdayani; Syed Agung Afandi; Muslim Afandi; Hijratul Aswad; Nail Hidaya Afandi (Sultan Syarif Kasim State Islamic University, Riau, 2022)
This study intends to discover the bias of Riau Pos in order to influence the actor's reputation in the nomination for Governor of Riau for 2024–2029. Through the lens of Faicrlough's text, discourse practice, and sociocultural practice, partisanship in the construction of reputation in news in the mass media is analyzed. The research data was gathered using a literature review and the listening technique. Fairclough's paradigm of critical discourse analysis was used to analyze the research data utilizing a comparable methodology. This study demonstrates that local political actors, such as Syamsuar, Edy Natar Nasution, Syamsurizal, Alfedri, Muhammad Adil, Abdul Wahid, and Achmad, have been influenced by the news in the Riau Pos concerning the 2024 Riau Governor election. Syamsuar, who is the Governor of Riau as well as the Chairman of the Regional Leadership Council Golkar Riau, appears to be a prominent figure in the published news. In addition to this, the media narrative has also contributed to Syamsuar's political image.